Fibroadenoma-like Lesion of the Vagina: A Description of 2 Cases of a Previously Unreported Entity. (March 2018) - Moore, Michelle; McKenna, Michael; Mandavilli, Srinivas; McCluggage, W. Glenn
Abstract : We report 2 cases of a previously undescribed vaginal lesion, which we term "fibroadenoma-like lesion of the vagina" because of the close morphologic resemblance to breast fibroadenoma. Both lesions arose in the upper vagina and exhibited a biphasic appearance with benign epithelial and stromal elements. The glandular epithelium comprised a double layer of luminal and basal cells with focal squamous differentiation in 1 case. The stromal component was fibroblastic and morphologically bland for the most part, although occasional atypical symplastic-like cells were present in 1 case. Both lesions exhibited a similar immunophenotype with the luminal and basal glandular epithelium expressing PAX8 and GATA3 while estrogen receptor and progesterone receptor were largely negative. The basal cell layer was p63 and CK5/6 positive. We discuss the possible origin and histogenesis of this rare lesion which we believe to be benign based on the morphologic features and uneventful 5 years follow-up in 1 case.